Objective structural clinical examination for evaluating learning efficacy of Cultural Competence Cultivation Programme for nurses - Yu-Hsia Lee (BMC Nursing, 2020)
Abstract Background Culture serves as an adhesive to bind the lives of people. There are no objective, useful tools to assess cultural competence and practice. In this study, we evaluated whether the cultural competence of nurses was strengthened through the Cultural Competence Cultivation Programme. Methods A quasi-experimental research design was used to evaluate nurses working at a medical centre in Taiwan. They were randomly allocated into an experimental group (n = 47), which received the Cultural Competence Cultivation Programme, or a control group (n = 50), which did not receive the educational programme. After the intervention, learning efficacy of the participants was assessed using an Objective Structured Clinical Examination (OSCE). The research data were statistically analysed on SPSS. Results The average score of the experimental group was significantly higher in the ‘communication ability and skill’ category. Furthermore, OSCE scores and Standardised Patient Survey assessment and total scores were significantly and positively correlated. Conclusion The findings of this study can serve as a reference for designing future clinical education programmes.